2023
DOI: 10.1002/adma.202207791
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Fillable Microrobotic Systems by Microfluidic Loading with Dip Sealing

Abstract: applications, including diagnostics and therapeutics. [1] Compared to traditionally passive nanomedicines, microrobots are active-matter systems composed of actuatable components including magnetic, [2] acoustic, [3] chemical, [4] and/or materials of biological origin. [5] These properties enable microrobots to navigate their environments and to perform highly specific tasks, such as penetrating deep tissues for drug delivery. Importantly, microrobotic systems can be engineered to perform different functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…225 (b) DLW-printed microfluidic system with one inlet for (i)-(iii) loading "microrobots" (i.e., magnetic liquid-core-shell particles) for drug delivery applications. 226 (c) DLW-printed microfluidic system with two inlets for culturing cell spheroids as well as mouse cumulus-oocyte-complexes and embryos. 227 on the use of commercial DLW printers from Nanoscribe GmbH-the authors used a NanoOne DLW printer from the company, UpNano GmbH, but also because the researchers leveraged a recent innovation for increasing the efficiency of DLW printing processes: "Dynamic Optical Tuning (DOT)".…”
Section: Future Directionsmentioning
confidence: 99%
“…225 (b) DLW-printed microfluidic system with one inlet for (i)-(iii) loading "microrobots" (i.e., magnetic liquid-core-shell particles) for drug delivery applications. 226 (c) DLW-printed microfluidic system with two inlets for culturing cell spheroids as well as mouse cumulus-oocyte-complexes and embryos. 227 on the use of commercial DLW printers from Nanoscribe GmbH-the authors used a NanoOne DLW printer from the company, UpNano GmbH, but also because the researchers leveraged a recent innovation for increasing the efficiency of DLW printing processes: "Dynamic Optical Tuning (DOT)".…”
Section: Future Directionsmentioning
confidence: 99%
“…For example, in 2022, Sun et al reported a procedure to print microcarriers that were filled through a microfluidic channel (see Figure 6A,B). [23] Filling of the carrier solution was possible after carefully designing the channels to control the surface tension, pressure, material waste, and connection between the system and the filling nozzle. After filling, the carriers were closed with a stimuli-responsive polycaprolactone sealing that released the encapsulated solution upon heating or NIR irradiation.…”
Section: D Printed Microfluidic Devicesmentioning
confidence: 99%
“…Adapted with permission. [ 23 ] Copyright 2023, The Authors. B) SEM cross‐section image of the drug carrier for the filling process.…”
Section: Microfluidicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Separating immiscible mixed liquids is a key step in pollutant treatment or resource recovery in daily life and industrial production. These mixtures contain complex organic solutions with a much smaller surface tension difference than those of oil–water mixtures. Separation of immiscible mixed organic liquids has great demands in the fields of biomedical applications and industrial chemistry, but the separation methods considerably fall behind the application requirements. Currently, very limited strategies have been introduced to separate these mixed organic liquids with low surface tension differences. For example, Tie et al developed a versatile coating that regulates the wetting behavior of membranes by forming a stable liquid injection interface and separating mixed organic liquids .…”
Section: Introductionmentioning
confidence: 99%